Contested Virilities: Constructing Masculinity in Dante's Tenzone with Forese. (March 2014) - Díaz, Sara E.
<x content-type="archive" xml:space="preserve">Abstract</x> This study explores the construction of Forese Donati's gendered identity in Dante's tenzone with Forese and, to a lesser extent, in the Purgatorio. The contradictory Forese episodes are analyzed in terms of gender practice and performance, and shown to be complementary representations of masculinity. I argue that as an aggressive contest for verbal dominance, the tenzone with Forese captures the dynamic struggle to assert hegemonic virility within Florence's urban aristocracy. Viewed through the lens of a society that placed specific demands upon the men entrusted with the care of their households, Forese's maleness is measured against his (in)ability to physically, economically, and affectively satisfy the needs of his wife. A gendered approach provides new insights into the nature of Dante's comic insults, and casts doubt on some of the basic assumptions behind palinodic readings that connect the two encounters with Forese.